Selected Decisions (3rd Ed). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1965)
This paper presents Selected Decisions and Selected Documents' Third Issue of the IMF. Dealings in paper money and coins are deemed to be 'other exchange transactions' within the meaning of Article IV, Section 3, whether or not the importation and exportation of such money and coins to and from the country of origin are subject to restrictions. The IMF does not object to exchange rates which are within 2 percent of parity for spot exchange transactions between a member's currency and the currencies of other members taking place within the member's territories, whenever such rates result from the maintenance of margins of no more than 1 percent from parity for a convertible, including externally convertible, currency. The Executive Directors interpret the Articles of Agreement to mean that steps which are necessary to protect a member from unemployment of a chronic or persistent character, arising from pressure on its balance of payments, are among the measures necessary to correct a fundamental disequilibrium; and that in each instance in which a member proposes a change in the par value of its currency to correct a fundamental disequilibrium the IMF will be required to determine, in the light of all relevant circumstances, whether in its opinion the proposed change is necessary to correct the fundamental disequilibrium.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet